Natural Experiment Demonstrates That Bird Loss Leads to Cessation of Dispersal of Native Seeds from Intact to Degraded Forests - Caves, Eleanor M.; Jennings, Summer B.; HilleRisLambers, Janneke; Tewksbury, Joshua J.; Rogers, Haldre S. (PLOS ONE, 2013)
In healthy forests, vertebrate frugivores move seeds from intact to degraded forests, aiding in the passive regeneration of degraded forests. Yet vertebrate frugivores are declining around the world, and little is known about the impact of this loss on regeneration of degraded areas. Here, we use a unique natural experiment to assess how complete vertebrate frugivore loss affects native seed rain in degraded forest. All native vertebrate frugivores (which were primarily avian frugivores) have been functionally extirpated from the island of Guam by the invasive brown tree snake (Boiga irregularis), whereas the nearby island of Saipan has a relatively intact vertebrate frugivore community. We captured seed rain along transects extending from intact into degraded forest and compared the species richness, density and condition of the seed rain from native bird-dispersed tree species between the two islands. Considering seeds from native bird-dispersed species, approximately 1.66 seeds landed per 26 days in each square meter of degraded forest on Saipan, whereas zero seeds landed per 26 days per square meter in degraded forest on Guam. Additionally, on Saipan, 69% of native bird-dispersed seeds in intact forest and 77% of seeds in degraded forest lacked fleshy fruit pulp, suggesting ingestion by birds, compared to 0% of all seeds on Guam. Our results show an absence of seed rain in degraded forests on Guam, correlated with the absence of birds, whereas on Saipan, frugivorous birds regularly disperse seeds into degraded forests, providing a mechanism for re-colonization by native plants. These results suggest that loss of frugivores will slow regeneration of degraded forests on Guam.